Effects of microwave-assisted pyrolysis on the microstructure of bituminous coals. (15th November 2019) - Li, He; Shi, Shiliang; Lin, Baiquan; Lu, Jiexin; Ye, Qing; Lu, Yi; Wang, Zheng; Hong, Yidu; Zhu, Xiangnan
Abstract: Microwave-assisted pyrolysis (MWAP) provides distinctive heating for the conversion of coal into liquid fuels. This work investigated the effects of MWAP on the microstructure of bituminous coals by using Fourier transform infrared spectroscopy (FTIR), mercury intrusion porosimetry (MIP) and Scanning Electron Microscope (SEM) techniques. FTIR results showed that MWAP can lead to the decomposition of oxygen functional groups and aliphatic hydrocarbons. Removal of these hydrophilic groups significantly weakens the hydrophilicity of coal. With continuous exposure to microwaves, unstable components such as alcohol, phenol and carboxylic acid are converted into ether groups. Cyclization and aromatization induced by microwave heating improve the maturation of coal. MIP and SEM results indicated that the jet force exerted by the high-pressure steam and gaseous products under MWAP gives a great boost to the opening, enlargement and connection of pores. Furthermore, the thermal stresses induced by microwave selective heating enlarge the fractures and create new cracks, providing seepage space for fluids. MWAP of bituminous coals can not only release moisture and volatiles but also create seepage space by modifying the pore and fracture structure. Highlights: Effects of microwave on the microstructure of bituminous coals were analyzed. Microwave irradiation can lead to the decomposition of oxygen functional groups. Microwave heating induces the opening, enlargement and connection of pores. Thermal stresses caused by microwave selective heating can generate fractures.